ASSESSING THE IMPACT OF DIGITAL MEDIA ON SPORTS DEVELOPMENT IN IMO STATE - Nnah, Florence C. (African Journal of Social and Behavioural Sciences, 2021)
The study is aimed at assessing the impact of digital media on sports development in Nigeria with focus on Imo State. The specific objectives of the study were to: examine the impact of owned media on sports development in Imo State; assess the influence of paid media on sports development in Imo State and determine the contribution of earned media to sports development in Imo State. The study employed a mix-method research design, in which systematic integration of quantitative and qualitative data were applied within the single study‟s investigation. The targeted population of the study comprised all of the members and executives of the Imo State Sport Council and the recently established Imo State Sports Commission. The study employed purposive sampling method for the selection of the respondents of the research‟s survey. A total of 170 respondents were selected to make up the sample size, comprising: executives, coaches and athletes in the Imo State Sports Council and the Imo State Sports Commission. A structured (close-ended) questionnaire was used to elicit information from the 170 respondents in the selected sample. For the qualitative data, key informant interview was conducted on executives in the existing five (5) zonal structures of sports in the State (Orlu, Owerri, Okigwe, Aboh Mbaise and Oru West). The collected data from the questionnaire process was analysed using quantitative analysis technique (descriptive and inferential statistical tools) and presented in tables, while the qualitative data collected in the interview was analysed using thematic analysis process. The study found that digital media (owned media, paid media and earned media) can have significant impact on developing the sport industry in Imo state and Nigeria at large. The study also found that digital media use is still at its infancy level in Imo state sport sector and has room for growth; furthermore, the engagement of digital media in sports is one of the most significant issues in the sports industry all over the world. The study recommended that government and stakeholders provide the necessary infrastructures and funding for the use of digital media for the development of sport industry in Imo State.